2023
DOI: 10.1186/s13023-023-02627-3
|View full text |Cite
|
Sign up to set email alerts
|

The patient clinical journey and socioeconomic impact of osteogenesis imperfecta: a systematic scoping review

Abstract: Background Osteogenesis imperfecta (OI) is a rare heritable connective tissue disorder primarily characterised by skeletal deformity and fragility, and an array of secondary features. The purpose of this review was to capture and quantify the published evidence relating specifically to the clinical, humanistic, and economic impact of OI on individuals, their families, and wider society. Methods A systematic scoping review of 11 databases (MEDLINE, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 278 publications
1
13
0
Order By: Relevance
“…While OI is equally prevalent in men and women, most direct respondents to the survey were female. This is in line with past patient-reported outcomes research in OI, where an increased participation of women with OI and female caregivers is common [ 9 ]. Most direct respondents were from Europe and European respondents made up > 50% of participants.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…While OI is equally prevalent in men and women, most direct respondents to the survey were female. This is in line with past patient-reported outcomes research in OI, where an increased participation of women with OI and female caregivers is common [ 9 ]. Most direct respondents were from Europe and European respondents made up > 50% of participants.…”
Section: Discussionsupporting
confidence: 89%
“…This was achieved through an ambitious and self-driven collaboration between the clinical and OI communities, aided by third-party funding from a pharmaceutical manufacturer. Past research on the impact of OI on individuals and their caregivers has been limited by small sample sizes and did not cover the breadth of topics included in IMPACT [ 6 , 7 , 9 , 18 , 19 ]. Therefore, IMPACT was designed as an online survey to maximise accessibility across geographies and included questions covering a breadth of topics exploring the clinical, humanistic, and economic impact of OI that may be insufficiently documented in the existing literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They also reported that 33% of OI patients had at least one unerupted tooth and that the prevalence of tooth eruption was associated with disease severity because type III patients showed the highest prevalence of unerupted teeth (70%), followed by type IV (40%), and type I (30%) (Taqi et al, 2021). Thus, treatment is challenging because the dental phenotypes vary according to the type of OI (Marini & Dang Do, 2000; Okawa et al, 2017; Rapoport et al, 2023). Compared to patients with type I OI, types III, and IV patients require more special intervention in their primary dentition because of more severe dentinogenesis imperfecta.…”
Section: Influence Of These Diseases On Dental Treatmentmentioning
confidence: 99%